Capacitor Bank Placement Enhancement Using Grey Wolf Algorithm for Reducing Harmonics in Low-Voltage Radial Distribution Networks - Happy Aprillia; Oik Rizki Septianto; Barokatun Hasanah; Suratno Suratno (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Low-voltage distribution systems are increasingly affected by harmonic distortion due to nonlinear loads, leading to power losses, reduced efficiency, and poor power quality. Capacitor banks are commonly used for reactive power compensation; however, improper placement may worsen harmonic conditions due to resonance effects. Objective: This study aims to optimize capacitor bank placement in a low-voltage radial distribution system while improving power quality and minimizing harmonic distortion using the Grey Wolf Optimizer (GWO). Method: A quantitative, simulation-based approach was applied using a 12-bus radial distribution model of an integrated laboratory system. Power flow analysis was conducted using the Backward/Forward Sweep (BFS) method, while optimization of capacitor placement and sizing was performed using the Grey Wolf Optimizer (GWO), considering multi-objective criteria including power loss, total harmonic distortion of current (THDI), total harmonic distortion of voltage (THDV), and power factor. Result: The proposed GWO allocated a total of 1000 kVAr across selected buses, resulting in a 4.41% reduction in active power loss, a decrease in THDV from 6.181% to 1.517%, and an improvement in power factor to unity (1.0 pu). However, THDI remained at 18.71%, exceeding IEEE 519-2014 limits, indicating the need for additional harmonic filtering solutions. Conclusion: The Grey Wolf Optimizer (GWO) is effective for optimizing capacitor placement and improving voltage-related power quality. However, additional harmonic mitigation techniques are required to comprehensively address current distortion.